MULTILINGUALISM IN ANCIENT WORLD ACCORDING TO THE ANCIENT LITERARY TRADITION (Philological Studies, 2019)
The paper addresses multilingualism as a cultural phenomenon in the ancient world according to the ancient Greek and Latin literary tradition. Hence, special attention is given to the Greek - Latin bilingualism, but also to the numerous data on the ancient spoken languages, including the language of the ancient Macedonians.
Keywords: antiquity, multilingualism, ancient literature, bilingualism, Latin language, ancient Greek language